USABILITY TESTING PADA ANTARMUKA KATALOG DARING SLIMS 8.0 AKASIA DI PERPUSTAKAAN BNPB - Danang Dwijo Kangko; Wisnu Ananta Kusuma; Pudji Muljono (Jurnal Pustakawan Indonesia, 2017)
AbstractLibrary catalogues are used to search collections and simplify the retrieval process. Currently, most library catalogues have built in the online form known as the Online Public Access Catalog (OPAC). The OPAC interface is important because it plays as a medium for connecting people with applications or systems. The interface can determine theeffectiveness and efficiency of the software. It analyzed by usability testing. The usability testing has not been conducted on Senayan Library Management System (SLiMS) OPAC interface. This research aims to analyze the usability of the SLiMS's OPAC interface at the Library of Indonesian National Disaster Management Agency (BNPB Library).The research conducted by Checklist and Think Aloud method. This research result identifies the shortcomings of the SLiMS-based OPAC interface in BNPB Library. Keywords: Interface, Online Public Access Catalog, SLiMS Senayan, Usability Testing